PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF CREATIVE DEVELOPMENT OF CHILDREN UNDER CONDITIONS ART-PEDAGOGICAL CABINET - E. Akhmedova (Вестник Северо-Кавказского федерального университета)
This article deals with the problem of psychological and pedagogical support of the creative development of children in the conditions of the art-pedagogical office. The purpose of the article is to identify and substantiate the psychological and pedagogical conditions for the creative development of children in the conditions of an art pedagogical oice. The results of the research described in the article can serve as practical material for the work of teachers and psychologists ofpreschool educational institutions who use art-pedagogical technologies for the creative development of children in their activities. Accumulated theoretical material can be proposed for use by teachers of pre-school educational institutions for the design of an art-pedagogical oice, which is one of the main forms of creative development and acts as a factor developing the creative abilities of preschoolers.